Decreased levels of serum platelet-activating factor acetylhydrolase in patients with rheumatic diseases - P. Vergne; V. Praloran; R. Treves; Y. Denizot (Hindawi Limited, 1997)
PAF is a potent inflammatory compound known to stimulate the release of various cytokines involved in rheumatic diseases. Elevated blood PAF levels are reported in these patients. We report that serum PAF acetylhydrolase activity (AHA) levels are decreased in patients with rheumatoid arthritis or osteoarthritis as compared to healthy controls. Serum and synovial fluid AHA levels were correlated in these patients. The present study suggests the potential role of AHA in controling systemic and/or local PAF levels in patients with rheumatic diseases.